Number and size of last-glacial Missoula floods in the Columbia River valley between the Pasco Basin, Washington, and Portland, Oregon - Benito, Gerardo; O'Connor, Jim E. (Geological Society of America, 2003)
Field evidence and radiocarbon age dating, combined with hydraulic flow modeling, provide new information on the magnitude, frequency, and chronology of late Pleistocene Missoula floods in the Columbia River valley between the Pasco Basin, Washington, and Portland, Oregon. More than 25 floods had discharges of >1.0 x 106 m3/s. At least 15 floods had discharges of >3.0 x 106 m3/s. At least six or seven had peak discharges of >6.5 x 106 m3/s, and at least one flood had a peak discharge of 10 x 106 m3/s, a value consistent with earlier results from near Wallula Gap, but better defined because of the strong hydraulic controls imposed by critical flow at constrictions near Crown and Mitchell Points in the Columbia River Gorge. Stratigraphy and geomorphic position, combined with 25 radiocarbon ages and the widespread occurrence of the ca. 13 ka (radiocarbon years) Mount St. Helens set-S tephra, show that most if not all the Missoula flood deposits exposed in the study area were emplaced after 19 ka (radiocarbon years), and many were emplaced after 15 ka. More than 13 floods perhaps postdate ca. 13 ka, including at least two with discharges of >6 x 106 m3/s. From discharge and stratigraphic relationships upstream, we hypothesize that the largest flood in the study reach resulted from a Missoula flood that predated blockage of the Columbia River valley by the Cordilleran ice sheet. Multiple later floods, probably including the majority of floods recorded by fine- and coarse-grained deposits in the study area, resulted from multiple releases of glacial Lake Missoula that spilled into a blocked and inundated Columbia River valley upstream of the Okanogan lobe and were shunted south across the Channeled Scabland. Peer reviewed